Examining the Benefits of Hybrid Solar Systems for the Production of Sustainable Energy - Dhanraj S. Degure (International Journal of Energy and Thermal Applications, 2023)
A state-of-the-art energy solution, the hybrid solar system combines solar photovoltaic (PV) panels and solar thermal collectors to provide an effective and flexible method of capturing solar energy. The hybrid solar system maximises the use of sunshine to produce energy and heat concurrently by integrating two technologies. While solar thermal collectors catch solar heat energy and transform it into useful thermal energy for a variety of purposes, solar PV panels convert sunlight directly into electricity. High energy efficiency and system performance are guaranteed by the hybrid system's intelligent design, which optimises the synergy between these two technologies. The system also includes sophisticated control mechanisms that enable smooth integration with the current power grid and energy storage systems, increasing its overall dependability and flexibility.
Keywords: Charging controller; DCDB; Hybrid invertor; Solar Panel